AKIBAT HUKUM ANAK HASIL BAYI TABUNG DAN INSEMINASI DI INDONESIA DAN FILIPINA - Hadi, Andi Ibnu (Institut Nahdlatul Ulama Tasikmalaya, 2024)
There are similarities and differences in legal regulations on IVF and insemination between Indonesia and the Philippines and have an impact on the status and legal standing of children. This article aims to determine the comparative legal consequences of IVF children in Indonesia and the Philippines. This study uses a comparative and normative juridical approach. From the results of the study, there are differences and similarities in the legal consequences for IVF children and insemination in Indonesia and the Philippines both from the aspect of civil law and from the aspect of criminal law.